2010
DOI: 10.1111/j.1600-0528.2010.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of a nutritional program in reducing early childhood caries: a randomized trial

Abstract: Home nutritional advice during the first year of life decreases caries incidence and severity at four years of age in a low income community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(155 citation statements)
references
References 30 publications
6
137
1
11
Order By: Relevance
“…Stronger effects were observed in São Leopoldo, where counseling in the same guidelines was provided directly to mothers (Feldens et al, 2010b). The impact on exclusive breastfeeding in Porto Alegre (Bernardi et al, 2011) was also weaker than that observed in São Leopoldo (Vítolo et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Stronger effects were observed in São Leopoldo, where counseling in the same guidelines was provided directly to mothers (Feldens et al, 2010b). The impact on exclusive breastfeeding in Porto Alegre (Bernardi et al, 2011) was also weaker than that observed in São Leopoldo (Vítolo et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…These 715 mother-child pairs were enrolled at baseline, prior to the decision that dental outcomes would be assessed. For this study, we aimed to detect a 25% relative reduction in the prevalence of caries at 2 to 3 yrs, while expecting 55% prevalence in the control group and 30% loss to followup, based on interpolation from the São Leopoldo study (Feldens et al, 2010b), which measured caries at different ages. At an alpha of 5% (two-sided) and a design effect of 1.5, this available sample would have 71% power for the outcome ECC.…”
Section: Statistical Powermentioning
confidence: 99%
“…Studies demonstrate that the instructions provided to the mother on the oral hygiene and diet of the infant helped in decreasing the incidence and severity of early childhood caries as well as ECC damaging effects on the children at long term [16,17]. Thus, the evaluation of the habits change because of the instructions received in prevention and education programs are important.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous dental MI studies targeting infants whose oral health is predominantly taken care of by their parents [15,21,22], this study focuses on preschoolers who are at a stage of forming their own health habits [12]. While the impact of early intervention (from infancy or even prenatal) is supported by sizeable scientific evidence [15,21,33,34], preschool age represents another window for behavioral intervention, because children’s food preference is being shaped [35], their toothbrushing habits are being reinforced [4], and parents are often receptive to health messages during this period of time [9,36]. Interventions in this age group are both promising and challenging.…”
Section: Discussionmentioning
confidence: 99%